PENGARUH KETERLIBATAN ORANG TUA TERHADAP AKHLAK SISWA - Afifah Sari, Ruli; Bahrodin, Ariga (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research aims to determine the influence of parental involvement on student morals. This research uses a quantitative approach, and the type of research used is a survey. The results show that there is an influence between parental involvement and student morals. This is known from the results of the level correlation test (Spearman rank). Researchers produced a significance value of 0.007 which is lower than 0.05. Based on the basis of decision making, there is an influence between variables x and y if the significance value is less than 0.05, but there is no influence between variables x and y if the significance value is higher. Apart from that, it is known that the coefficient number is 0.353, which means it has a positive value, which means that when X and Y increase, there is a unidirectional relationship, and the coefficient classification is at a low level of strength/relationship.